The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/atmos11090996
|View full text |Cite
|
Sign up to set email alerts
|

Did ERA5 Improve Temperature and Precipitation Reanalysis over East Africa?

Abstract: Reanalysis products are often taken as an alternative solution to observational weather and climate data due to availability and accessibility problems, particularly in data-sparse regions such as Africa. Proper evaluation of their strengths and weaknesses, however, should not be overlooked. The aim of this study was to evaluate the performance of ERA5 reanalysis and to document the progress made compared to ERA-interim for the fields of near-surface temperature and precipitation over Africa. Results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 63 publications
8
122
2
Order By: Relevance
“…In Africa, the local overestimation of precipitation over Lake Victoria, Lake Tanganyika, and the Ethiopian highlands is in agreement with existing literature (Gleixner et al, 2020). Over the northern Great plains in North America in summer, we observe a slight dry bias as in Xu et al (2019), in the western part of the region.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…In Africa, the local overestimation of precipitation over Lake Victoria, Lake Tanganyika, and the Ethiopian highlands is in agreement with existing literature (Gleixner et al, 2020). Over the northern Great plains in North America in summer, we observe a slight dry bias as in Xu et al (2019), in the western part of the region.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…For daily mean, maximum and minimum temperature, we used ERA5 data 24 provided at a spatial resolution of 0.25° × 0.25°. ERA5 is the most recent reanalyses product and outperforms ERA-Interim for East Africa 25 . The weather variables were created for the time period of available yield statistics (2009–2019), including weather data for the year 2008 in case of growing seasons starting already at the end of 2008.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the quality of near-surface temperatures in ERA5, Oueslati et al (2017) and Barbier et al (2018) assessed ERA-Interim, which ERA5 is an improvement of, against the Global Summary Of the Day (GSOD) observational dataset, and concluded that it was suitable for heatwave study in the Sahel. Furthermore, Gleixner et al (2020) showed that in ERA5, near-surface temperatures are less climatologically biased, and their interannual variability better represented than in ERA-Interim across Africa, including in the Sahel band. Similarly, Wang et al (2017), Tall et al (2019), Wright et al (2020) and Hersbach et al (2020) proved that ERA5 represents relatively well the observed OLR over the tropical domain, confirming its suitability as reference dataset for the analysis of tropical modes.…”
Section: Description Of the Ecmwf Ens Extended-range Forecasting Systemmentioning
confidence: 99%